Ocean deoxygenation dampens resistance of diatoms to ocean acidification in darkness - Sun, Jia-Zhen; Zhang, Di; Yi, Xiangqi; Beardall, John; Gao, Kunshan (Frontiers in Marine Science, 2024)
Respiratory activity in the oceans is declining due to the expansion of hypoxic zones and progressive deoxygenation, posing threats to marine organisms along with impacts of concurrent ocean acidification. Therefore, understanding the combined impacts of reduced pO2 and elevated pCO2 on marine primary producers is of considerable significance. Here, to simulate diatoms’ sinking into the aphotic zone of turbid coastal water, we exposed the diatoms Thalassiosira pseudonana and Thalassiosira weissflogii in darkness at 20°C to different levels of pO2 and pCO2 conditions for 3 weeks, and monitored their biomass density, photosynthetic activity and dark respiration, and examined their recovery upon subsequent exposure to light at 20°C, simulating surface water conditions. Along with decreased cell abundance and size, measured photosynthetic capacity and dark respiration rates in these two diatoms both gradually decreased during the prolonged darkness. Reduced pO2 alone did not negatively affect the photosynthetic machinery in both the dark-survived diatom, and enhanced their subsequent recovery upon light exposure. Nevertheless, the combination of the elevated pCO2 and reduced pO2 (equivalent to hypoxia) led to the biomass loss by about 90% in T. pseudonana, and delayed the recovery of both species upon subsequent exposure to light, though it did not reduce the cell concentration of T. weissflogii during the elongated darkness. Our results suggest that reduced O2 availability diminishes the abilities of the diatoms to cope with the acidic stress associated with ocean acidification, and the expansion of hypoxic waters could delay the photosynthetic recovery of coastal diatoms when they are transported upwards through mixing from dark layers to sunlit waters.